1994
DOI: 10.1183/09031936.94.07010074
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-interferon modifies guinea pig airway functions in vitro

Abstract: Cytokines produced by T-lymphocytes may have significant roles in the airway inflammation seen in bronchial asthma. Gamma interferon (IFN-gamma), a T-cell derived cytokine, is known to modify functions of both immune and non-immune cells. In this study, we investigated whether IFN-gamma can modify guinea pig airway functions in vitro. The isometric tension of guinea pig airway strips was measured in a tissue bath filled with Krebs-Henseleit solution. Contracting responses to carbachol and KCl, and the relaxing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…IFN-c enhances LTD 4 -induced contraction in human ASM cells 115 and ASM sensitivity to isoproterenol in guinea pig ASM. 116 In contrast, Hakonarson et al 65 showed that IFN-c prevents asthmatic serumeinduced alterations in ASM responsiveness to either acetylcholine or isoproterenol. Although the JAK/STAT1 pathway is usually the primary component of the IFN-c signaling cascade, Tliba et al 117 recently showed for the first time that TNF-a, via the autocrine activation of IFN-b receptoreassociated JAK1 and Tyk2, stimulates STAT1-dependent and STAT2-dependent gene expression in human ASM cells.…”
Section: Autocrine Effect Of Asm-derived Ifn-bmentioning
confidence: 94%
“…IFN-c enhances LTD 4 -induced contraction in human ASM cells 115 and ASM sensitivity to isoproterenol in guinea pig ASM. 116 In contrast, Hakonarson et al 65 showed that IFN-c prevents asthmatic serumeinduced alterations in ASM responsiveness to either acetylcholine or isoproterenol. Although the JAK/STAT1 pathway is usually the primary component of the IFN-c signaling cascade, Tliba et al 117 recently showed for the first time that TNF-a, via the autocrine activation of IFN-b receptoreassociated JAK1 and Tyk2, stimulates STAT1-dependent and STAT2-dependent gene expression in human ASM cells.…”
Section: Autocrine Effect Of Asm-derived Ifn-bmentioning
confidence: 94%
“…IFN-␥ may have direct effects on AHR by acting on airway smooth muscle. IFN-␥ was shown to inhibit airway smooth muscle contraction to carbachol, KCl, and TGF-␤ with isoproterenol (39,40) and to inhibit the proliferation of airway smooth muscle (41). Moreover, several studies have reported that intranasal administration of IFN-␥ effectively inhibited goblet cell metaplasia and AHR in a mouse model (34,35,42).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of tracheal rings obtained from guinea pig (20,135) and mice (161) and isolated smooth muscle cells (4) to inflammatory cytokines resulted in modulation of the responsiveness of airway smooth muscle to a variety of contractile and relaxant agents. Because calcium is a common second messenger molecule for a variety of contractile agonists in airway smooth muscle, we determined the effect of these cytokines on the intracellular calcium responses.…”
Section: Role Of Cd38/cadpr Signaling In Ahrmentioning
confidence: 99%